Anishinaabeg women’s stories of wellbeing: Physical activity, restoring wellbeing, and dismantling the settler colonial deficit analysis - McGuire-Adams, Tricia (Te Rau Ora, 2017)
The settler colonial lens deficit approach to Indigenous peoples’ health constructs us as ill, which sets the stage for our eventual erasure. In contrast to this deficit-based approach, in this paper I employed an Anishinaabeg research paradigm and followed Anishinaabeg protocols to understand how Anishinaabeg women are creating wellbeing for themselves, their families, and communities through engaging in physical activity. Based on seven interviews with Anishinaabeg women who are engaged in decolonized physicality, the Anishinaabeg women participants promote gwesayjitodoon indo bimaadiziiwin, which means to transform oneself into a better life. The participants showed how if one can apply the concept of gwesayjitodoon indo bimaadiziiwin to his or her physical activity, it has potential to enact broader community wellbeing that can confront the settler colonial deficit lens that requires Indigenous peoples’ erasure, and through which Aboriginal health research has for too long been examined.